Understanding and modeling finger vascular pattern imaging. Issue 5 (1st February 2022) - Normakristagaluh, Pesigrihastamadya; Laanstra, Geert Jan; Spreeuwers, Luuk; Veldhuis, Raymond
Abstract: In this paper, new insights in the near infrared imaging process used in finger‐vein recognition by developing a physical model are presented. A realistic phantom finger that mimics the living human finger and also includes veins has been developed to validate this model. NIR phantom finger images show that the phantom can emulate the optical properties of a living human finger and can provide ground truth for the locations of the veins. Through physical modeling, it is particularly learned that—besides blood and soft tissue—bone also plays an important role in generating reliable NIR finger‐vein images.